Perlindungan Konsumen Terhadap Makanan Pangan Industri Rumah Tangga - Ernawati Ernawati (Lembaga Penelitian dan Pengabdian Masyarakat, 2017)
Consumers have the freedom to determine the type and quality of the goods/services in accordance with their needs. Food safety, quality problems and the impact of irregularities, as well as the strengths, weaknesses, opportunities and threats in the development of food industry quality system is a shared responsibility as the consumer protection efforts. The method in this research using qualitative methods. The research results showed that consumer protection conducted by government agencies and other institutions in the following way i.e. perform monitoring of food products by giving the number of the PIRT against businessmen who are qualified and have previously received counseling about the food products that may be released, as well as to provide warning and withdrawal of products that contain a positive dye textiles. The efforts made by the North Buton Regency POM Halls namely collaborates with government agencies and Institutions Consumers North Buton Regency to do surveillance, sampling and testing, guidance products. Trade a proven violation reported to the District Health Office of North Buton for follow up. Restricting factors for the Government and Consumers North Buton Regency in coping with a circulation of foods that contain colouring substances in textiles, namely budget constraints to organise activities agenda so that there are no activities were carried out, bureaucratic system which is still so convoluted follow-up to businessmen.